The Queer Voices of Xavier Dolan’s Mommy - Jason R. D’Aoust (European Journal of American Studies, 2017)
This article examines the vocal materialities of Xavier Dolan’s film Mommy (2014). It focuses on the film’s swearing, competing diegetic voices, disruptive soundtrack, as well as its scenes of lip synch, play-back, and karaoke, in order to convey queer vocal identifications. The article’s interdisciplinary methodology includes audiovisual theories of the voice-object, post-Lacanian psychoanalysis, and revisions of the voice’s place in queer theories via critiques of videocentrism.